Implementation of Regional Regulation Number 4 of 2018 by the Bangkalan Regency Government in an Effort to Reduce Flood Intensity in Arosbaya District Reviewed from Islamic Law - Siti Maysaroh; Abdul Rokhim; Diyan Isnaeni (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
Flooding is a recurring environmental problem in Arosbaya Sub-district, Bangkalan Regency, which calls for an integrated and context-specific mitigation approach. This qualitative descriptive study examines flood mitigation efforts through the lens of community perceptions, policy implementation, and alignment with Islamic legal values. Data were collected through field observations, interviews, and documentation involving stakeholders such as BPBD Bangkalan, PUPR, and affected residents. Findings show that Regional Regulation No. 4 of 2018 provides a structured disaster mitigation framework, comprising pre-disaster (disaster-resilient villages and early warning systems), emergency response (evacuation, temporary shelters, and public kitchens), and post-disaster (rehabilitation of infrastructure and socio-economic recovery). These efforts are underpinned by Islamic legal principles including Hifz al-Nafs, Al-Ta’awun ‘ala al-Birr wa al-Taqwa, Al-Ihsan, Al-Takaful al-Ijtima’i, Islah, and Al-Tazkiyah al-Nafs, which emphasize the sanctity of life, collective responsibility, mutual aid, and moral development. However, the implementation faces significant obstacles such as limited resources, low public participation, inadequate early warning systems, poor inter-agency coordination, and the neglect of local wisdom. Although the community shows strong commitment, a lack of disaster education and limited access to information hamper active engagement. This study contributes by offering a normative-empirical model that integrates Islamic law with contemporary disaster mitigation frameworks, recommending enhanced public outreach, stronger institutional collaboration, and the incorporation of local knowledge to achieve more sustainable and inclusive flood mitigation strategies